Nobel Lecture: The Economic Way of Looking at Behavior - Becker, Gary S. (Journal of Political Economy, 1993)
An important step in extending the traditional theory of individual rational choice to analyze social issues beyond those usually considered by economists is to incorporate into the theory a much richer class of attitudes, preferences, and calculations. While this approach to behavior builds on an expanded.theory of individual choice, it is not mainly concerned with individuals. It uses theory at the micro level as a powerful tool to derive implications at the group or macro level. The lecture describes the approach and illustrates it with examples drawn from the author's past and current work.